THE EFFECT OF PROFIT AND CASH FLOW IN PREDICTING FINANCIAL DISTRESS (STUDY OF TRANSPORTATION COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2019 – 2021 PERIOD) - Fharah Fauziah Nauli; Dini Arwaty (SEAN Institute, 2022)
The business world in this era is developing more rapidly and is followed by increasingly sophisticated technological developments. This development will certainly cause new problems in the industrial sector, one of which is the strengthening of the level of competition. In addition, in 2020 the world was hit by Covid-19iwhich had a negativeiimpact onithe health, economiciconditions,ieducation, and social lifeiof theiIndonesian people. Poor management in such a situation will pose a threat of bankruptcy to the company. This studyiaims to test the effect of profit andicash flow inipredicting financialidistress conditions in transportation companies listedion the IndonesiaiStock Exchange forithe 2019-2021 period. The data used in this studyiwas taken fromiwww.idx.co.id website. The method usediin this studyiis quantitative descriptive analysis. A total of 40 companies in thisistudy were sampled, namely transportation companies listed onithe Indonesia StockiExchange for the 2019-2021iperiod, using purposive sampling with certain criteria. The results ofithis study show that profit affects financialidistress while cash flow does not affect financial distress initransportation companies listedion the IndonesiaiStock Exchange.